2018
DOI: 10.1158/1078-0432.ccr-18-1126
|View full text |Cite
|
Sign up to set email alerts
|

Local Phototherapy Synergizes with Immunoadjuvant for Treatment of Pancreatic Cancer through Induced Immunogenic Tumor Vaccine

Abstract: To develop a synergistic combination therapy for advanced pancreatic cancer, using local phototherapy and immunotherapy, and to determine the efficacy and mechanism of the novel combination therapy using a highly metastatic pancreatic tumor model in mice. Mice bearing Panc02-H7 pancreatic tumors (both subcutaneous and orthotopic) were treated with noninvasive or interventional photothermal therapy, followed by local application of an immunoadjuvant. Tumor growth and animal survival were assessed. Immune cell p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 46 publications
(45 reference statements)
0
59
0
Order By: Relevance
“…Zhou et al showed that mice treated with photothermal therapy (PTT) alone had a significant smaller tumor burden than that of the control mice. A 10‐minutes treatment with 980 nm laser at a density of 0.85 W/cm 2 (510 J/cm 2 in total) increased the temperature of tumor tissue, which caused cell death in mouse models of pancreatic cancer and melanoma . In this approach, heat generation in tissues is considered to induce immunologic cell death with release of heat shock proteins (HSPs), calreticulin (CRT), high‐mobility group box 1 (HMGB1) protein, and adenosine triphosphate (ATP) .…”
Section: Ultrashort Pulsed Laser Adjuvantmentioning
confidence: 93%
See 1 more Smart Citation
“…Zhou et al showed that mice treated with photothermal therapy (PTT) alone had a significant smaller tumor burden than that of the control mice. A 10‐minutes treatment with 980 nm laser at a density of 0.85 W/cm 2 (510 J/cm 2 in total) increased the temperature of tumor tissue, which caused cell death in mouse models of pancreatic cancer and melanoma . In this approach, heat generation in tissues is considered to induce immunologic cell death with release of heat shock proteins (HSPs), calreticulin (CRT), high‐mobility group box 1 (HMGB1) protein, and adenosine triphosphate (ATP) .…”
Section: Ultrashort Pulsed Laser Adjuvantmentioning
confidence: 93%
“…A 10-minutes treatment with 980 nm laser at a density of 0.85 W/cm 2 (510 J/cm 2 in total) increased the temperature of tumor tissue, which caused cell death in mouse models of pancreatic cancer and melanoma. 33 In this approach, heat generation in tissues is considered to induce immunologic cell death with release of heat shock proteins (HSPs), calreticulin (CRT), high-mobility group box 1 (HMGB1) protein, and adenosine triphosphate (ATP). 34 In response to this, DCs are stimulated and produce IFN-γ and increase their expression of MHCII and CD80 and recruitment of DCs and T cells in tumor microenvironment.…”
Section: Non-pulsed Laser Adjuvantmentioning
confidence: 99%
“…An interventional PTT using an optical fiber with a NIR light of 980 nm was inserted into tumor center and an immunoadjuvant agent of glycated chitosan (GC) was intratumor-injected immediately after PTT in mouse pancreatic tumor model. The complete regression was achieved and more importantly, it triggered tumor-specific immune memory and the production of memory T cells to inhibit tumor rechallenge (Zhou et al, 2018). Ma et al (2019) adopted a second NIR (NIR II at 1086 nm) light to carry out the PTT.…”
Section: Photothermal Therapy Synergized Immunotherapymentioning
confidence: 99%
“…Laser immunotherapy (LIT) was developed to achieve this objective. LIT has two components: 1) local photothermal therapy (PTT) for disrupting target tumor homeostasis and releasing tumor antigens (12,13), and 2) local administration of an immunostimulant, such as N-dihydrogalactochitosan (GC) (14,15). In preliminary clinical studies for patients with metastatic, treatment-recalcitrant breast cancer and melanoma, LIT successfully reduced and/or eliminated the treated primary tumors and untreated metastases in the lungs (16-18).…”
Section: Introductionmentioning
confidence: 99%